EXPLORING CAVES - Rathburn, Betsy; Downs, Kieran; Brink, Josh (Minneapolis, MN : Bellwether Media, 2023)
Deep inside the earth lie undiscovered wonders that have never seen the light of day. In this title, readers will learn how bold explorers venture into the darkness of caves. Vibrant photos show readers what it is like to explore caves, while special features map a well-known cave, highlight the preparation needed to explore caves, introduce a famous cave explorer, and more. Readers will be eager to explore more after finishing this exciting adventure!
Includes index
Bibliography : page 23
Ages 7-12 Grades 4-6
Keywords: Outdoor life -- Juvenile literature; Outdoor recreation -- Juvenile literature; Extreme sports -- Recreations -- Juvenile literature; Caves -- Juvenile literature